Diffusion-Weighted Magnetic Resonance Imaging of an Intramedullary Epidermoid Cyst with Dorsal Dermal Sinus Tract in a Toddler. (22nd October 2013) - Fazio, Michael G.; Kil, Alyson M.; Rooks, Veronica J.; Biega, Timothy J.
Abstract : We report the use of diffusion-weighted magnetic resonance imaging to diagnose and manage a rare case of a symptomatic thoracic intramedullary congenital epidermoid cyst with associated dermal sinus in a girl. Congenital intramedullary epidermoid cysts with associated dermal sinuses are very rare occurrences and seldom present symptomatically in very young children. We present a case of a 32-month old with a draining dimpled skin lesion. Magnetic resonance images demonstrated an intramedullary epidermoid with a dorsal dermal sinus tract opening to the skin surface which was confirmed surgically. The patient was treated with debulking to prevent recurrent infection and progression of neurological symptoms. This case demonstrates the use of diffuse-weighted MRI to assist in the diagnosis and surgical management of an atypical presentation of a rare developmental abnormality, which is not well documented in the pediatric radiological literature. Failure to diagnosis may have significant neurological permanent debilitating consequences.